Issues, Challenges, and Coping Mechanisms of Out-of-Field Physical Education Teachers in Subject Delivery - Rivero, Josua (Journal of Interdisciplinary Perspectives, 2024)
This study explored the challenges and coping mechanisms of out-of-field Physical Education (PE) teachers. A descriptive-correlational design was employed with 30 out-of-field PE teachers as respondents. Data gathering tools included a survey questionnaire, while statistical treatments comprised Weighted Mean, Pearson Product-Moment Correlation Coefficient, and Determination of Coefficient. It was found that most respondents encountered issues, with the learning environment being less of a concern. Additionally, most respondents disagreed that supervisory assistance was evident in the curriculum, posing a challenge for out-of-field PE teachers. Seeking support from colleagues was identified as the most prominent coping mechanism, indicating a strong need for collaboration. However, other coping mechanisms were not strongly utilized by teachers. The influence of coping mechanisms varied across different issues and challenges. Finally, policy recommendations were developed based on the study's findings to support out-of-field PE teachers.